The Comparison of The Effect of Profitability, Solvency and Firm Size on Firm Value: (Empirical Study Sub-Sector Companies on Food and Beverage and Sub-Sector Companies on Cosmetic and Household Listed on Indonesia Stock Exchange Period 2015-2019) - Felisita Ferdinanda; Rilla Gantino (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2021)
This study aims to analyze the Comparison of The Effect of Profitability, Solvency and Firm Size on Firm Value of Empirical Study Companies in Food and Beverage and Cosmetics Sub-Sector Manufacturing Companies and Households Listed on the Indonesia Stock Exchange in 2015-2019. The method used in this study is non probability sampling or saturated sample technique. The number of samples used in this study was 19 food and beverage companies and 5 cosmetic and household companies, bringing the total sample to 24 companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. A data type is secondary data sourced from financial statements and annual reports. The data analysis method used is multiple linear regression analysis. Hypothetical test results show that simultaneously Profitability, Solvency and Firm Size have a significant impact on the Firm Value. Partial profitability has a significant and positive effect on the Firm Value in food and beverage sub-sector companies, while Profitability has no effect on the Firm Value in cosmetic and household sub-sector companies. Solvency has a significant and positive effect on the Firms Value in food and beverage sub-sector companies and cosmetic and household sub-sector companies. The Firm size has no significant effect on the Firm Value in food and beverage sub-sector companies and cosmetic and household companies.